Estudo taxonômico e morfométrico dos gêneros Terschellingia e Pseudolella (Nematoda) em estuários tropicais no Brasil (7°S) - Barros, Fábio Lucas de Oliveira (2022)
Nematode are abundant and diverse in all ecosystems on earth. Knowledge about the species diversity of these organisms is still scarce. Small size, morphological variations, species identifications mostly based on male individuals and high representation of juvenile individuals in the environment are difficulties for a broader understanding of the Nematode taxonomy. The present study aimed to analyze the taxonomy of the genera Terschellingia and Pseudolella, abundant in tropical estuaries, using morphological and morphometric characters. Samples were collected in 2016 in two estuaries in Paraiba – NE, Brazil (7°S). The nematodes were submitted to diaphanization and permanent slides were made and the specimens were measured with a curvimeter in an optical microscope with a drawing tube. Linear regression analyzes were used to evaluate the relationships between variations in morphometric characteristics and the variation in total body size between juvenile and adults, including male and female, ontogenetic stages. ANCOVA was used to test differences between ontogenetic stages in morphometric relationships. A total of 194 specimens of the genera Terschellingia and Pseudolella were analyzed, in which 102 individuals are of the genus Terschellingia, all identified as Terschellingia longicaudata and 92 of the genus Pseudolella, proposed here Pseudolella sp. n. 1, represented by 86 individuals and six individuals identified as Morphotype 1. In Terschellingia longicaudata, diagnostic features were based on morphological and morphometric data. In Pseudolella, proportions were required for a good diagnosis, reducing morphometric variation. Both genera had great morphometric variation. Both genera had great morphometric variation. These variations, in most cases, were related to the variation of the total body size. However, between ontogenetic stages, diagnostic features do not significantly differ from the variations. The morphometric analyzes allow the evaluation of the variation of the main diagnostic characteristics, making it a good tool to discuss the characteristics of problematic genera of the phylum Nematode. The occurrence of morphometric characteristics, without significant differences in the variation in juvenile, female and male stages, combined with morphological data, allow the identification of species of the genera Terschellingia and Pseudolella, regardless of the ontogenetic stage.